Invesitigation of Malware and Forensic Tools on Internet - Tarun Kumar; Sanjeev Sharma; Ravi Dhaundiyal; Parag Jain (International Journal of Electrical and Computer Engineering (IJECE), 2018)
Malware is an application that is harmful to your forensic information. Basically, malware analyses is the process of analysing the behaviours of malicious code and then create signatures to detect and defend against it.Malware, such as Trojan horse, Worms and Spyware severely threatens the forensic security. This research observed that although malware and its variants may vary a lot from content signatures, they share some behaviour features at a higher level which are more precise in revealing the real intent of malware. This paper investigates the various techniques of malware behaviour extraction and analysis. In addition, we discuss the implications of malware analysis tools for malware detection based on various techniques.